Influence of major depressive disorder and culture on emotion processing among adults - Mohan, Sindhu (2019)
Depression is a mood disorder that appears to affect a large number of people worldwide at an escalating rate. Impairments in emotion processing and regulation have been found to cause depression. Delving through research related to depression revealed a lack of investigation into the areas of emotion processing and culture. Hence, this gap is bridged by comparing adults with and without Major Depressive Disorder (MDD) from a particular culture (Malaysian Malay), as well as a comparison of adults without MDD from three cultures (Malays, Australians, and Iranians) to determine the variance in emotion processing. The general aim of Phase 1 of this study was to investigate the influence of participant condition on emotion processing among adults with and without MDD, while Phase 2 aimed to investigate the influence of culture on emotion processing among Malaysian Malays, Australian Caucasians, and Iranian Persians. This study was based on Matsumoto and Hwang’s Biocultural Model of Emotion and Triandiss’ Subjective Cultural model. In Phase 1 of this study a total of 107 Malaysian Malay participants with and without MDD were examined. Participants completed five experiments, which were (a) facial emotion recognition (FER), (b) biological motion recognition (BMR), (c) biological emotion recognition (BER), (d) subjective experience (SE), and (d) emotion meaning (EM). The participants were also required to complete five questionnaires, which were Beck Depression Inventory (BDI), Self-Construal Scale (SCS), Individualism- Collectivism scale (IndCol), WHO Quality of Life scale (WHOQOL-BREF), and the Emotion Regulation Questionnaire (ERQ). In Phase 2, 106 Malaysian Malay, Australian Caucasian and Iranian Persian participants without MDD were evaluated. Participants completed all experiments as Phase 1, except the FER, whereas in this phase they only completed the BDI, SCS, and IndCol. All the participants were between 18 and 60 years old. The outcomes from Phase 1 showed non-significant differences between participants with and without MDD in FER and BM experiments. As for the SE experiment, participants with MDD exhibited more negative emotions, when compared to participants without MDD. Similarly, for the EM experiment, participants with MDD thought that their social worth had decreased after experiencing a negative event and they strongly believed that they were responsible such event. Nevertheless, those with MDD were more likely to share their emotions with others regardless of the event being positive of negative. In Phase 2, no difference was noted between Malaysians, Australians, and Iranians in the biological emotion recognition (BER) experiment but, they differed in the biological motion recognition (BMR) experiment. In the SE and EM experiments, only certain emotions were associated with particular cultures. The type of emotion experienced relied on the type of situation. In conclusion, the study outcomes seemed to concur with the results reported in prior studies, which showed that adults with MDD had biased attention and perception towards negative stimuli and that emotion processing was influenced by cultural differences.